2024
DOI: 10.7717/peerj.16785
|View full text |Cite
|
Sign up to set email alerts
|

Altered O-linked glycosylation in benign and malignant meningiomas

Chutima Talabnin,
Thanawat Trasaktaweesakul,
Pitchanun Jaturutthaweechot
et al.

Abstract: Background Changes in protein glycosylation have been reported in various diseases, including cancer; however, the consequences of altered glycosylation in meningiomas remains undefined. We established two benign meningioma cell lines—SUT-MG12 and SUT-MG14, WHO grade I—and demonstrated the glycan and glycosyltransferase profiles of the mucin-type O-linked glycosylation in the primary benign meningioma cells compared with two malignant meningioma cell lines—HKBMM and IOMM-Lee, WHO grade III. Changes in O-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…It has been demonstrated that MUC1 participates in multiple signaling pathways and plays a pivotal role in cancer development, metastasis, metabolism, apoptosis, proliferation, and drug resistance [ [32] , [33] , [34] , [35] ]. Recent study revealed that MUC1 expression was highly increased in malignant meningiomas in the GEO database and MUC1 may play essential role in the progression of meningioma, however, the exact mechanism is still unclear [ 36 ]. Based on these findings, MUC1 has been identified as a promising diagnostic, therapeutic and prognostic target in epithelial cancers [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MUC1 participates in multiple signaling pathways and plays a pivotal role in cancer development, metastasis, metabolism, apoptosis, proliferation, and drug resistance [ [32] , [33] , [34] , [35] ]. Recent study revealed that MUC1 expression was highly increased in malignant meningiomas in the GEO database and MUC1 may play essential role in the progression of meningioma, however, the exact mechanism is still unclear [ 36 ]. Based on these findings, MUC1 has been identified as a promising diagnostic, therapeutic and prognostic target in epithelial cancers [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%